Debt versus Equity—Open Innovation to Reduce Asymmetric Information - Arief Yulianto; Rini Setyo Witiastuti; Widiyanto (Journal of Open Innovation: Technology, Market and Complexity, 2021)
ABSTRACT: The research aims to examine the difference between absence and presence life cycle stage in technology information digitalization (TID) as a form of open innovation in reducing information asymmetry. Furthermore, companies with asymmetric information prefer debt over equity. The study collects 3.343 pooled data observation units of companies listed in the Indonesian capital market period 2008 to 2019. We use OLS regression analysis to determine the difference between the absence and presence lifecycle stage in determining capital structure relations and exploiting growth opportunities. The study found information disclosure obligation of the capital market regulator has not been fully disclosed through TID. As a result, companies choose to pass in growth opportunities with debt or equity in the absence life cycle stage. Presence lifecycle stage, in the introduction stage, the company misses growth opportunities. Growth and mature stage, debt has a positive effect on the utilization of growth opportunities. The company prefers the issuance of debt with lower information sensitivity than equity. Presence culture, such as majority ownership, generates incentives for open innovation from capital market regulators, which still contain information asymmetry.